Letter : Spanish refugee metal workers - Schevenels, Walther, b. 1894
027-0066-001 INTERNATIONAL FEDERATION OF TRADE UNIONS 9, AVENUE D'ORSAY, PARIS-VIIe Sch/H TELEGRAMS: INTERFED-PARIS TELEPHONE: INVALIDES 43-88 AFFILIATED COUNTRIES: ARGENTINE BELGIUM CANADA CHINA CZECHOSLOVAKIA DENMARK DUTCH EAST INDIES ESTONIA FINLAND FRANCE GREAT BRITAIN HOLLAND HUNGARY INDIA LUXEMBURG MEXICO NEW ZEALAND NORWAY PALESTINE POLAND RUMANIA SPAIN SWEDEN SWITZERLAND UNITED STATES YUGOSLAVIA EXECUTIVE COMMITTEE: President: W. M Citrine, Great Britain Vice-Presidents: H. Jacobsen, Denmark; L. Jouhaux, France; E. Kupers, Holland; M. Miester, Switzerland; Corn. Mertens, Belgium General Secretary: W. Schevenels Letter. Sec. ref. div. No. 1158 30th August, 1939. Mr. H. V. Tewson, London. Dear Comrade Tewson, SPANISH REFUGEE METAL WORKERS I have read with care the letter from Comrade Carrillo to the TUC, of which a copy is attached to your letter of the 23rd August, and I am afraid Carrillo is right in saying that the non-Communist Spanish metal workers do not find much - if any - support from the French Metal Workers' Federation. But it is another question whether we can intervene in this matter. Apart from the present political situation, which makes it impossible to deal with such questions at the moment, it would under normal circumstances be difficult to interfere, since the present leaders of the Federation, with one or two exceptions, are all Communists. This situation may change very rapidly as a consequence of Russia's political treason, but, as I say above, the time is hardly propitious for action to be taken. If the situation is cleared up, we shall of course be glad to take the steps required. Yours sincerely, W. Schevenels, General Secretary. 292/946/27/66